MODEL PEMBERDAYAAN WANITA KELOMPOK PKK KELURAHAN KEDUNGWULUH PURWOKERTO - Tri Septin Muji Rahayu; Wida Purwidianti; Sulistyani Budiningsih (Universitas Peradaban, 2014)
This article will appoint three problems faced by the population, especially women or groups of women PKK RT 01 and RT 02 RW 08 Sub Kedungwuluh in an effort to increase the family income is limited acknowledge entrepreneurial knowledge of the process of manufacturing and marketing products and instant ginger scented financial management effort. Solution partners to solve problems are done by counseling, training and business mentoring instant ginger fragrance. Outcomes or results to be achieved is a partner becomes an entrepreneur who can produce and market a fragrance Ginger to increase family income and can conduct business financial management ginger scented correctly.Activities that have been implemented are doing and how entrepreneurship education ginger plant breeding, training of making ginger scented instant, training, marketing and manufacturing of simple financial statements. The results of the activities are already partners have knowledge of entrepreneurial, able to make and market their products and make instant ginger scented simple financial statements of the business conduct clinical trials of products, partners follow food safety education in the Department of Health, makes packaging and promotional media fragrant ginger instant products, PIRT certification filed at the Department of Health to be widely marketed.